Implementation of European Environmental Policy in Ukraine: Problems and Prospects - Ladychenko, Viktor; Golovko, Liudmyla (European Journal of Sustainable Development, 2017)
The purpose of our scholarly work is to explore actual problems of harmonization of environmental legislation of Ukraine with the requirements and principles of EU environmental policy and development of proposals for the improvement of Ukrainian legislation. Main features of harmonization of Ukrainian legislation in the sphere of environmental protection and prospects for improvement of legal liability of business entities which activity is highly hazardous for violation of environmental law were analyzed. As a result of the study draft law "On prevention and elimination of damage caused to the environment" was elaborated. The authors also developed State concept of realization of human rights to qualitative and safe drinking water, basic concept of which was reflected in the article. Keywords: Environmental policy, environmental safety, drinking water quality, adaptation of Ukrainian environmental legislation to EU standards.